The neural determinants of perceptual decision-making in the human brain - Twomey, Deirdre M. (Trinity College (Dublin, Ireland). School of Psychology, 2017)
Perceptual decision making is the process through which sensory information is translated into adaptive action. It is a fundamental brain function that is at the heart of human behaviour and is necessary for the successful performance of any cognitive task. Basic perceptual decisions are composed of at least three essential processing stages: sensory encoding, decision formation, and motor execution. In recent years, studies of animal neurophysiology have greatly elucidated the neural dynamics underpinning each of these stages. Most importantly, this body of work demonstrated that the intermediate decision stage is achieved by accumulating sensory evidence for the decision over time until a reliable quantity has been gathered. Such accumulation-to-bound dynamics accord with the long-standing predictions of mathematical models and can explain how the brain facilitates adaptive action in the face of sensory information that is often noisy. These breakthroughs generated considerable excitement across the broad field of neuroscience as they provided a framework for exploring the flow of information from sensation through to action in a comprehensive and mechanistically principled way. However, despite these advances, much is still to be learned about the brain’s decision-making machinery and how it is implicated in the neurobiology of psychiatric disorders ...
Keywords: Psychology, Ph.D.; PhD Trinity College Dublin, 2017